Effects of child labor upon the health of the child worker (2004)
OBJECTIVES: This article presents a review of the evidence on child labor, in three aspects: 1. The characteristics of children which make them vulnerable to labor; 2. The diseases and accidents related with child labor, and 3. The injuries associated with the childs' occupations, such as agriculture, construction, manufacture, textiles, leather industry, street sales and sales in marketplaces. METHODS: The Medline, EBSCO, PROQUEST and HINARI databases were searched, and material from the International Labor Organization, the American Academy of Pediatrics and the American Association of Psychology was reviewed. RESULTS: Information regarding occupational risk in children is poor as compared with information in adults. Children have characteristics which make them particularly vulnerable to occupational risks and there are no clear standards to protect them.